Pandangan Dunia Tragis dalam Legenda Wadu Ntanda Rahi Suku Bima di Kota Bima Nusa Tenggara Barat - Wibowo, Ari; Rokhmansyah, Alfian; Dahlan, Dahri (Universitas Mulawarman, 2021)
This study aims to describe the tragic worldview in the legend of Wadu Ntanda Rahi. This research is field research. The data of this research is the legend of Wadu Ntanda Rahi, the version of the people who live in the coastal part of Bima. The informants are the Bima Tribe, who was born, settled, and have lived in Bima City and know the legend of Wadu Ntanda Rahi. This study's data collection techniques were interviews and documentation using oral literature documentation forms, transcription, and translation. According to Goldmann, data analysis was carried out using a tragic world analysis model on the legend of Wadu Ntanda Rahi. The results show that in the legend of Wadu Ntanda Rahi, there is a tragic fate experienced by the two main characters in the story, namely La Nggusu (husband) and La Nggini (wife). La Nggusu suffered a tragic fate because he migrated who never returned to his hometown. La Nggusu's departure as a husband made La Nggini's life be lived alone. La Nggini often gets tragic things in her life. Her husband's departure was the beginning of La Nggini's tragedy, followed by the death of her closest family, which made her even more alone, until in the end, she hoped to become immortal, namely to become a stone. La Nggini's suffering is the result of the absence of God, the silent world, and the result of tragic human traits that demand the impossible.